2021
DOI: 10.3390/jof7090724
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into Defense Responses of Vietnamese Maize Varieties to Fusarium verticillioides Isolates

Abstract: Fusarium ear rot (FER) caused by Fusarium verticillioides is one of the main fungal diseases in maize worldwide. To develop a pathogen-tailored FER resistant maize line for local implementation, insights into the virulence variability of a residing F. verticillioides population are crucial for developing customized maize varieties, but remain unexplored. Moreover, little information is currently available on the involvement of the archetypal defense pathways in the F. verticillioides–maize interaction using lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Also, BXs-dependent resistance of maize toward Spodoptera littoralis , a leaf feeder, has been reported ( Maag et al, 2016 ). In agreement with Tran et al (2021c) , F. verticillioides induced the upregulation of the BXs genes in leaves of line Bt/GT NK7328. This finding might be helpful for one who wants to develop FER-resistant maize lines associated with these genes.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Also, BXs-dependent resistance of maize toward Spodoptera littoralis , a leaf feeder, has been reported ( Maag et al, 2016 ). In agreement with Tran et al (2021c) , F. verticillioides induced the upregulation of the BXs genes in leaves of line Bt/GT NK7328. This finding might be helpful for one who wants to develop FER-resistant maize lines associated with these genes.…”
Section: Discussionsupporting
confidence: 73%
“…After uncovering the direct antagonism of the biocontrol strain on maize seedlings by the reduction of the DNA level of F. verticillioides in soil ( Figure 4 ), we explored whether the growth of plants was impacted. To examine this, we used two hybrid maize lines CP888 and Bt/GT NK7328 predominantly planted in the central highlands of Vietnam ( Tran et al, 2021c ). For line CP888, the growth of plants infected with the fungus (FV + W) was negatively affected with significantly lower fresh leaf and root biomass weight when compared to the control non-infected plants ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-one fungal species comprising saprophytic and pathogenic ones were detected, in which their percent infestation was variable according to the locations. Our results revealed that maize seeds were infected by varying degrees with several pathogenic fungi, like F. verticillioides , F. proliferatum , Alternaria alternata , Drechslera maydis, and S. strictum, which are the primary causal agents of pink ear rot, Alternaria leaf blight, Southern corn leaf blight, and wilt diseases in most world maize-growing areas [ 39 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sarocladium zeae was previously described as producing extracellular hydrolases, e.g., cellulases, amylases, and proteases [ 47 ], which are reported to play a role in the host-pathogen interaction; these enzymes were also reported in our isolates. On the other hand, a recent study identified S. zeae as the beneficial endophyte in maize seeds [ 42 ]. This contradiction may be due to the presence of different strains having, or not, various pathogenic activities on plants.…”
Section: Discussionmentioning
confidence: 99%